Health Communication Study in the Digital Era: Analysis of Handling Diabetes Mellitus Discourse in Indonesia in 10 Years (2015-2025) - Rosita Kumala Dewi; Mutia Rahmi Pratiwi (Jogjakarta Communication Conference (JCC), 2025)
Diabetes Mellitus (DM) sufferers globally continue to increase every year, based on data from the International Diabetes Federation (IDF), sufferers are projected to reach 783 million in 2045. Not only parents, diabetes cases also attack Indonesian children. This is certainly a severe issue that needs to be handled by various parties. This research was conducted to analyze various digitalization efforts carried out by the government, academics, business actors, media, and society within a period of 10 years (2015-2025) to reduce the number of diabetes sufferers in Indonesia. This research method uses qualitative with a Text Analysis approach. The theory used is the Pentahelix Model which involves five main actors, namely: academics, industry, government, community, and media. The research results show that the government is implementing the PTM, GERMAS, PIS-PK, GGL, and the National Campaign to Prevent and Treat Diabetes. Various digital communities were formed by the community, such as Sobat Diabet, Persadia, Blue Circle the Indonesian Diabetes Community, and SobatDIA. From an academic perspective, research on Diabetes was carried out from 2016 -2024 but the perspective was taken from the perspective of medical personnel communication and there were two studies on designing visual media to inform about diabetes in 2019 and 2023. It is hoped that the results of this study can become strategic recommendations for stakeholders in improving health communication to reduce the number of diabetes sufferers in Indonesia through various education on digital pages.